# Rewrite in Standard Form (y-3)=-2/3*(x+4) (y-3)=-23⋅(x+4)
The standard form of a linear equation is Ax+By=C.
Remove parentheses.
y-3=-23⋅(x+4)
Multiply both sides by 3.
3(y-3)=3(-23⋅(x+4))
Simplify 3(y-3).
Apply the distributive property.
3y+3⋅-3=3(-23⋅(x+4))
Multiply 3 by -3.
3y-9=3(-23⋅(x+4))
3y-9=3(-23⋅(x+4))
Simplify 3(-23⋅(x+4)).
Apply the distributive property.
3y-9=3(-23x-23⋅4)
Combine x and 23.
3y-9=3(-x⋅23-23⋅4)
Multiply -23⋅4.
Multiply 4 by -1.
3y-9=3(-x⋅23-4(23))
Combine -4 and 23.
3y-9=3(-x⋅23+-4⋅23)
Multiply -4 by 2.
3y-9=3(-x⋅23+-83)
3y-9=3(-x⋅23+-83)
Simplify each term.
Move 2 to the left of x.
3y-9=3(-2⋅x3+-83)
Move the negative in front of the fraction.
3y-9=3(-2×3-83)
3y-9=3(-2×3-83)
Simplify terms.
Apply the distributive property.
3y-9=3(-2×3)+3(-83)
Cancel the common factor of 3.
Move the leading negative in -2×3 into the numerator.
3y-9=3-2×3+3(-83)
Cancel the common factor.
3y-9=3-2×3+3(-83)
Rewrite the expression.
3y-9=-2x+3(-83)
3y-9=-2x+3(-83)
Cancel the common factor of 3.
Move the leading negative in -83 into the numerator.
3y-9=-2x+3(-83)
Cancel the common factor.
3y-9=-2x+3(-83)
Rewrite the expression.
3y-9=-2x-8
3y-9=-2x-8
3y-9=-2x-8
3y-9=-2x-8
Move all terms containing variables to the left side of the equation.
Add 2x to both sides of the equation.
3y-9+2x=-8
Move -9.
3y+2x-9=-8
Reorder 3y and 2x.
2x+3y-9=-8
2x+3y-9=-8
Move all terms not containing a variable to the right side of the equation.
Add 9 to both sides of the equation.
2x+3y=-8+9
2x+3y=1
2x+3y=1
Rewrite in Standard Form (y-3)=-2/3*(x+4)     